A computational approach for spider web‐inspired fabrication of string art. (26th June 2019) - Je, Seungwoo; Abileva, Yekaterina; Bianchi, Andrea; Bazin, Jean‐Charles
Abstract: Creating objects with threads is commonly referred to as string art. It is typically a manual, tedious work reserved for skilled artists. In this paper, we investigate how to automatically fabricate string art pieces from one single continuous thread in such a way that it looks like an input image. The proposed system consists of a thread connection optimization algorithm and a custom‐made fabrication machine. It allows casual users to create their own personalized string art pieces in a fully automatic manner. Quantitative and qualitative evaluations demonstrated our system can create visually appealing results. Abstract : Inspired by the spiders' ability to build intriguing and sophisticated web structures using just a single continuous thread, we investigate how to automatically fabricate planar objects and string art from one single continuous thread (no cut, no glue) in such a way that it looks like an input image. The proposed system consists of a thread connection optimization algorithm and a custom‐made fabrication machine. Quantitative and qualitative evaluations have demonstrated that our system can create visually appealing results.